Cancer‐specific mortality, cure fraction, and noncancer causes of death among diffuse large B‐cell lymphoma patients in the immunochemotherapy era. Issue 17 (2nd May 2017) - Howlader, Nadia; Mariotto, Angela B.; Besson, Caroline; Suneja, Gita; Robien, Kim; Younes, Naji; Engels, Eric A.
Abstract : BACKGROUND: Survival after the diagnosis of diffuse large B‐cell lymphoma (DLBCL) has been increasing since 2002 because of improved therapies; however, long‐term outcomes for these patients in the modern treatment era are still unknown. METHODS: Using Surveillance, Epidemiology, and End Results data, this study first assessed factors associated with DLBCL‐specific mortality during 2002‐2012. An epidemiologic risk profile, based on clinical and demographic characteristics, was used to stratify DLBCL cases into low‐, medium‐, and high‐risk groups. The proportions of DLBCL cases that might be considered cured in these 3 risk groups was estimated. Risks of death due to various noncancer causes among DLBCL cases versus the general population were also calculated with standardized mortality ratios (SMRs). RESULTS: Overall, 8274 deaths were recorded among 18, 047 DLBCL cases; 76% of the total deaths were attributed to DLBCL, and 24% were attributed to noncancer causes. The 10‐year survival rates for the low‐, medium‐, and high‐risk groups were 80%, 60%, and 36%, respectively. The estimated cure proportions for the low‐, medium‐, and high‐risk groups were 73%, 49%, and 27%, respectively; however, these cure estimates were uncertain because of the need to extrapolate the survival curves beyond the follow‐up time. Mortality risks calculated with SMRs were elevated for conditions including vascular diseases (SMR, 1.3), infections (SMR, 3.1), gastrointestinal diseases (SMR, 2.5), and blood diseases (SMR, 4.6). These mortality risks were especially high within the initial 5 years after the diagnosis and declined after 5 years. CONCLUSIONS: Some DLBCL patients may be cured of their cancer, but they continue to experience excess mortality from lymphoma and other noncancer causes. Cancer 2017;123:3326‐34 . © 2017 American Cancer Society . Abstract : Some patients with diffuse large B‐cell lymphoma may be cured of their cancer but continue to experience excess mortality from lymphoma and other noncancer causes in the immunochemotherapy era. Clinicians should be aware of recently published strategies for the long‐term medical care of survivors of diffuse large B‐cell lymphoma. See also pages 3222‐5.